How international students of colour become Black: a story of whiteness in English higher education. Issue 1 (2nd January 2022) - Madriaga, Manuel; McCaig, Colin
ABSTRACT: This article highlights how international students of colour are racialised in English higher education. Key performance indicators of racial inequality in the sector like achievement outcomes currently discount experiences of international students of colour. This is problematic as international students, as found in this study, identify themselves under the sector racial category of Black and minority ethnic (BME). They experience racism and discrimination in and outside the Academy just like 'home' BME students. The work presented here foregrounds the racialised experiences of international students of colour in English higher education. It is a counter-story in the tradition of critical race theory which reveal how whiteness unifies and divides. It unifies in creating a shared experience amongst those who experience the heat of the 'white gaze' in academia. It divides, categorising and classifying 'us' to the extent that 'we', both students and academic staff, may unwittingly perpetuate whiteness.